Tertiary Nitrifying Moving Bed-Biofilm Reactor: A Study of Carrier and Loading Effects on Nitrifying Kinetics, Biologically Produced Solids and Microbial Community - Forrest, Daina (Université d'Ottawa / University of Ottawa, 2014)
There is an increasing need for tertiary level wastewater treatment in Canada, driven in some cases by both provincial and federal regulation (Canada Gazette, 2012). Tertiary nitrification is the biologically mediated oxidation of nitrogen in the form of ammonia to nitrate following secondary treatment of carbonaceous material (Barnes & Bliss, 1983). The application of tertiary nitrification can prove challenging in the Canadian climate because of the temperature sensitive nature of nitrifiers (Hwang & Oleszkiewicz, 2007). Hence the greater than 1000 lagoon treatment plants currently in operation throughout country are susceptible to the full onslaught of weather effects and as such their nitrification processes become non-existent during the winter months (Delatolla et al., 2011,Hoang et al., 2014). The moving bed biofilm reactor (MBBR) system has been studied and shows promise for continuous nitrification with prolonged exposure to cold temperatures (Hoang et al., 2014). They are marketed as cost effective and low operation intensive upgrade options for existing treatment plants as well as effective stand-alone systems and are currently in operation in many countries worldwide (WEF, 2011). Despite the MBBRs initial development as a nitrification technology, recent research has been focused on COD removal systems. Studies showing that MBBR performance is directly related to surface area loading rates (SALRs) and not carrier type or shape have been performed exclusively on COD removal systems. The influence of MBBR carrier type on system solids production has also been solely studied for COD removal and the principles learnt have been transferred to tertiary nitrification systems without confirmation that they hold true. There is an absence of research on tertiary nitrifying kinetics; the effect of loading and carrier type, the nature of the solids produced and the carrier biofilm characteristics. This study investigated three MBBR carrier types, the K3, M and P Anoxkaldnes carriers in an effort to quantify the effects of carrier type on nitrifying kinetics, biologically – produced solids and the bacterial community at normal and high loading conditions. Four tertiary nitrifying laboratory scale MBBRs were fed with synthetic wastewater and operated at a high loading condition (HLC) with a SALR of 1.89 ± 0.10 g-N/m2•d and a normal loading condition (NLC) with SALR of 0.91 ± 0.1 g-N/m2•d. At both HLC and NLC, results show no difference in the ammonia removal rates obtained by the different carrier types. It was however noticed that stressed operational conditions developed for the P and M carrier at the HLC due to the clogging of carrier pore spaces with biofilm and subsequent reductions in removal efficiency were observed. Despite the fact that larger surface area to volume carriers (such as the M and P) may lead to MBBR designs with smaller footprints and lower operational cost, the study revealed their greater propensity to become clogged under high loading conditions than the smaller surface area carriers (such as the K3 ). In addition the larger surface area carriers demonstrated longer transitional periods from high loading conditions to lower loading conditions. A reduction in effluent total suspended solids (TSS) concentrations and improved solids settleability was observed with the shift from HLC to NLC. These results suggest the avoidance of high loading conditions in tertiary nitrifying MBBR operation. If low loading rates are not achievable then system design may have to consider the incorporation of coagulant use or an advanced solids separation technique to meet effluent solids regulation. Variable pressure scanning electron microscope (VPSEM) images at HLC showed the presence of water mites on the K3 carrier and nematodes and ciliates on the M and P carriers. While NLC images do not show these organisms. VPSEM also measured thicker biofilms during the HLC than the NLC for all carriers. The results demonstrate a difference in the meso-environments and suggest a difference in the micro-environments of the biofilm attached to each carrier. Microbial analysis showed no shifts in the dominant nitrifying species between the loading conditions, as well as no differences in the percent live /dead cell coverage. Nitrosomonas and Nitrospira were identified as the dominant AOB and NOB genera respectively at both the HLC and the NLC. Clear shifts in the microbial populations were observed for specific bacteria; with filamentous bacteria being observed at greater relative abundance at HLC than HLC. The increased relative abundance of filamentous organisms are also associated with the significantly poorer effluent settling characteristics observed at HLC.
Keywords: nitrification; MBBR; Wastewater; carrier type